Soil Fertility Status of Research Farm Koont Fields, Rawalpindi, Punjab - Ullah, Muhammad Arshad; Afzal, Muhammad Usama; Siddique, Muhammad Tariq; Saleem, Muhammad Zeeshan (International Journal For Research In Agricultural And Food Science, 2019)
This study was conducted to assess the soil fertility status of olive, citrus, sunflower, maize and grapes fields of Research Farm, Koont, Rawalpindi. During the study soil samples of these fields were analyzed for pH, ECe and organic matter. The results of the soil analysis indicated that soil pH is alkaline due to calcareous nature of soil. It has a good pH value almost neutral which is optimum for maximum growth for most of the crops. Soil electrical conductivity of examined fields was less than 4 dSm-1. Electrical conductivity of these fields is normal, so there is no danger of the excessiveness of toxic salts. Citrus field is the best on because it has low ECe value. Organic matter ranged from 0.23 to 1.16 percent. Organic matter is also present in sufficient quantities which show soil is productive.